It will equal (4,6) for x and y
Answer:
<h2>One solution.</h2>
Step-by-step explanation:
The given question is
<em>Does the following system have One Solution, No Solution, or Infinite Solutions.
</em>
<em />
<em />
<em />
<em />
To solve this system, we just need to multiply the first equation by -1, and then sum those equations.
![-y = -4x - 8\\y = -5x + 3](https://tex.z-dn.net/?f=-y%20%3D%20-4x%20-%208%5C%5Cy%20%3D%20-5x%20%2B%203)
![0=-9x-5\\5=-9x\\x=-\frac{5}{9}](https://tex.z-dn.net/?f=0%3D-9x-5%5C%5C5%3D-9x%5C%5Cx%3D-%5Cfrac%7B5%7D%7B9%7D)
Then, we use this value to find the other one
![y=4x+8\\y=4(-\frac{5}{9} )+8\\y=-\frac{20}{9}+8\\y =\frac{-20+72}{9} \\y=\frac{52}{9}](https://tex.z-dn.net/?f=y%3D4x%2B8%5C%5Cy%3D4%28-%5Cfrac%7B5%7D%7B9%7D%20%29%2B8%5C%5Cy%3D-%5Cfrac%7B20%7D%7B9%7D%2B8%5C%5Cy%20%3D%5Cfrac%7B-20%2B72%7D%7B9%7D%20%5C%5Cy%3D%5Cfrac%7B52%7D%7B9%7D)
As you can observe, the system of equations have a unique solution.
Therefore, the answer is one solution.
Answer:
16.80 ft long
Step-by-step explanation:
Answer:
Step-by-step explanation:
f(x)=x+4(x^2+2x-3)=4x^2+9x-12
f'(x)=8x+9
f'(x)=0,gives x=-9/8
f(-5)=-5+4(-5-1)(-5+3)=-5+4*-6*-2=43
f(-9/8)=-9/8+4(-9/8-1)(-9/8+3)
=-9/8+4*-17/8*15/8
=-9/8-255/16
=-273/16=-17 1/16
f(5)=4*5^2+9*5-12=100+45-12=133
absolute maximum=133
absolute minimum=-17 1/16